Pengaruh Situation-Based Learning Terhadap Kemampuan Problem Posing Siswa - Roningsih, Roningsih; Isrok'atun, Isrok'atun; Gusrayani, Diah (Jurnal Pena Ilmiah, 2019)
Students lack confidence in expressing curiosity, then students tend to be shy in asking questions, which causes low problem posing abilities of students. Mathematics is inseparable from the submission of problems, so the problem posing ability is important for students to have. Therefore problem posing skills need to be trained and developed through SBL learning. The purpose of this study was to determine the effect of SBL learning on students' problem posing abilities. The method used in this study was quasi-experimental with a type of nonequivalent control group design. The study population used was all students of fifth grade elementary school in North Sumedang District. Sampling using purposive sampling technique. While the sample was taken from SDN Rancamulya. The instruments used in this study were problem posing ability test questions, attitude scale questionnaires, teacher performance observation sheets, student activities, and field notes. The results showed that SBL learning had a positive effect on students' problem posing abilities.